2022
DOI: 10.25259/sni_1150_2021
|View full text |Cite
|
Sign up to set email alerts
|

Delayed peritoneal shunt catheter migration into the pulmonary artery with indolent thrombosis: A case report and narrative review

Abstract: Background: Ventriculoperitoneal (VP) shunts are the preferred surgical treatment for hydrocephalus, and rarely, these operations may be complicated by catheter migration to ectopic sites. We present the case of an asymptomatic VP shunt patient with delayed peritoneal catheter migration into the pulmonary artery shunt catheter migration into the pulmonary artery (SCMPA) complicated by knotting and indolent thrombosis, necessitating open-heart surgery for system retrieval. Methods: We conducted a literature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Also, cardiac migration of VP shunt catheters mainly occurs in pediatric patients or individuals aged 60 and above. 14 15) In pediatric cases, it is assumed that the thin subcutaneous tissue in the neck makes jugular vein injury more likely. Conversely, in individuals aged 60 and above, the looser subcutaneous tissue may lead to more frequent vein injuries during procedures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, cardiac migration of VP shunt catheters mainly occurs in pediatric patients or individuals aged 60 and above. 14 15) In pediatric cases, it is assumed that the thin subcutaneous tissue in the neck makes jugular vein injury more likely. Conversely, in individuals aged 60 and above, the looser subcutaneous tissue may lead to more frequent vein injuries during procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Also, if vegetation has formed on the shunt catheter, there is also an embolic risk. Patel et al 14) reported that open heart surgery was performed to remove a knotted catheter migrated to the heart. Therefore, considering the possible risks, shunt catheter removal should be carefully performed in consultation with a cardiologist.…”
Section: Discussionmentioning
confidence: 99%
“…These risks of venous stenting should be explained to every patient consenting for the procedure but should be placed in context of the myriad risks that are inherent in CSF shunting. These include central nervous system infection and acute or delayed intraparenchymal hemorrhage, all of which can be fatal, 48,49 as well as ectopic migration of the peritoneal tip to sites as disparate as the pulmonary artery (often with secondary thrombosis), 50 mouth, 51 urethra, 52 or rectum. 53 In one single-center series of 95 patients treated with VPS over an 8-year period, 54 there were 5 severe complications, and one fatal, yielding a mortality rate of approximately 1%.…”
Section: Complicationsmentioning
confidence: 99%